El descrédito de la dialéctica discursiva - Chichi, Graciela Marta (Tópicos (México).)
The aim of this paper is to pay attention to an discredited conception of Dialectic, which pretended to recreate the Aristotle's account. The paper emphazises the philosophical background of the Schopenhauer's art of getting the best of an opponent in a dispute, and specially identifies both the old Greek discussion rules, and the positive and original issues of this modem account.